2019
DOI: 10.1002/jcp.29330
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐16 is involved in the pathogenesis of pre‐eclampsia via regulation of Notch2

Abstract: In recent years, the role of microRNAs (miRNAs) in pre-eclampsia (PE) has been demonstrated, while the relevant mechanisms of miR-16 in PE await to be unearthed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…NOTCH2 and NOTCH3 signaling antagonize each other in different cell systems [56][57][58][59], suggesting that these NOTCH receptors also have opposite functions in the antigen-dependent regulation of CD5+ (B-1a) B-cell homeostasis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…NOTCH2 and NOTCH3 signaling antagonize each other in different cell systems [56][57][58][59], suggesting that these NOTCH receptors also have opposite functions in the antigen-dependent regulation of CD5+ (B-1a) B-cell homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…The NOTCH3 gene is frequently epigenetically silenced in B-cell acute lymphocytic leukemia (B-ALL) cells, pointing to a broader tumor-suppressor role of NOTCH3 in B-cells [63]. Moreover, the CLL downregulated/deleted MicroRNA-16 [64] has been shown to exert its pro-apoptotic function by NOTCH2 inhibition in pre-eclampsia, where an inverse correlation between NOTCH2 and NOTCH3 expression also has been found [59].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differentially expressed miRNAs have been found in exosomes [ 50 , 64 , 103 , 112 ] and Mesenchymal stem cells (MSCs) [ 28 , 51 , 71 , 76 ] as well as in placental tissues and peripheral serum or plasma. For example, miR-16 upregulation was first confirmed in the placentas of patients with PE [ 29 ]. Studies have shown that miR-16 is differentially expressed in the decidual MSCs of patients with severe PE and normal patients, and can inhibit the proliferation and migration of decidual-derived MSCs by targeting cyclin E1 and inducing cell cycle arrest [ 28 ].…”
Section: Mirnas and Preeclampsiamentioning
confidence: 99%
“… [ 18 23 ] miR-182-5p placenta upregulated RND3 the increased miRNA-182-5p expression could inhibit the migratory and invasive ability of trophoblast cells through targeted degrading RND3 protein [ 24 ] miR-155 placenta/placenta-associated serum exosomes upregulated CYR61/Cyclin D1 Overexpression of miR-155 in HTR-8/SVneo cells inhibited cell invasion, proliferation and increased cell number at the G1 stage in trophoblast cells [ 16 , 25 ] miR-155-5p placenta upregulated eNOS miR-155 inhibited cell invasion in trophoblast cells, and the effect was rescued by over expression of eNOS. [ 26 ] miR-195 placenta downregulated ActRIIB/ActRIIA miR-195 could promote cell invasion via directly targeting ActRIIB/ActRIIA in human trophoblast cells [ 27 ] miR-16 placenta/mesenchymal stem cell (MSC) upregulated CCNE1 /VEGF-A/Notch2 over-expressed miR-16 inhibited the proliferation and migration of decidua-derived mesenchymal stem cells /BeWo and JEG-3 cells, and induced cell-cycle arrest by targeting cyclin E1 [ 28 , 29 ] miRNA-376c placenta/plasma/exosome downregulated ALK5/ALK7/25-OH-VD miR-376c inhibits both ALK5 and ALK7 expression to impair transforming growth factor-β/Nodal signaling, leading to increases in cell proliferation and invasion [ 30 , 31 ] miR-29b decidua-derived mesenchymal stem cell (dMSC)/placenta upregulated MMP2/MCL1/ VEGFA/ ITGB1/HDAC4 miR-29b induced apoptosis and inhibited invasion and angiogenesis of trophoblast cells. [ 32 ] miR-101 placenta downregulated ERp44/BRD4/CXCL6 miR-101 could promote apoptosis and inhibite the proliferation and migration of...…”
Section: Mirnas and Preeclampsiamentioning
confidence: 99%